Assessment of Public Perception Regarding Patient Engagement for Patient Safety in Korea. Issue 1 (January 2021) - Lee, Hyeon-Jeong; Jang, Seung Gyeong; Choi, Ji Eun; Lee, Won; Pyo, Jeehee; Ock, Minsu; Lee, Sang-Il
Abstract : Objectives: This study conducted a survey to examine how the general public in Korea perceives patient engagement for patient safety and to identify vulnerable groups and contents priorities of patient engagement education for the general public. Methods: We developed a questionnaire based on previous studies and conducted one-on-one interviews with 600 individuals from the public. Then, we conducted descriptive statistical analyses (i.e., frequency, percentage, and averages) on the questionnaire items. Furthermore, we examined the individual differences of participants' sociodemographic characteristics in their responses to the questionnaire. Results: The general public's awareness regarding accreditation programs for healthcare organizations was still low (47.4%). Nearly 60% of participants said that they did not agree with the practice of telling their own names and dates of birth before treatment. Approximately 80% of the participants would not ask medical staff to confirm washing their hands. Only half of the participants were aware of medical dispute mediation and arbitration programs. Nearly 90% of the participants agreed that patient safety is important. However, on participants' confidence in making the correct choice and safety in their treatment, the average score was 68.7 of 100 points. Participants tended to be less confident about engaging in patient safety activities if they were older, less educated, or had poor health status. Conclusions: Participants in this study believed that patient safety is an important issue, but they were not confident about choosing the correct medical institution or about receiving safe treatment. Abstract : Supplemental digital content is available in the text.